Effects of active and sham tDCS on the soleus H-reflex during standing. - McCane, Lynn M; Wolpaw, Jonathan R; Thompson, Aiko K (Exp Brain Res, 2023)
Weak transcranial direct current stimulation (tDCS) is known to affect corticospinal excitability and enhance motor skill acquisition, whereas its effects on spinal reflexes in actively contracting muscles are yet to be established. Thus, in this study, we examined the acute effects of Active and Sham tDCS on the soleus H-reflex during standing. In fourteen adults without known neurological conditions, the soleus H-reflex was repeatedly elicited at just above M-wave threshold throughout 30 min of Active (N = 7) or Sham (N = 7) 2-mA tDCS over the primary motor cortex in standing. The maximum H-reflex (H) and M-wave (M) were also measured before and immediately after 30 min of tDCS. The soleus H-reflex amplitudes became significantly larger (by 6%) ≈1 min into Active or Sham tDCS and gradually returned toward the pre-tDCS values, on average, within 15 min. With Active tDCS, the amplitude reduction from the initial increase appeared to occur more swiftly than with Sham tDCS. An acute temporary increase in the soleus H-reflex amplitude within the first minute of Active and Sham tDCS found in this study indicates a previously unreported effect of tDCS on the H-reflex excitability. The present study suggests that neurophysiological characterization of Sham tDCS effects is just as important as investigating Active tDCS effects in understanding and defining acute effects of tDCS on the excitability of spinal reflex pathways.
Keywords: Adult; Evoked Potentials, Motor; H-Reflex; Humans; Muscle, Skeletal; Standing Position; Transcranial Direct Current Stimulation

Methods for automated delineation and assessment of EMG responses evoked by peripheral nerve stimulation in diagnostic and closed-loop therapeutic applications. - McKinnon, Michael L; Hill, N Jeremy; Carp, Jonathan S; Dellenbach, Blair; Thompson, Aiko K (J Neural Eng, 2023)
Surface electromyography measurements of the Hoffmann (H-) reflex are essential in a wide range of neuroscientific and clinical applications. One promising emerging therapeutic application is H-reflex operant conditioning, whereby a person is trained to modulate the H-reflex, with generalized beneficial effects on sensorimotor function in chronic neuromuscular disorders. Both traditional diagnostic and novel realtime therapeutic applications rely on accurate definitions of the H-reflex and M-wave temporal bounds, which currently depend on expert case-by-case judgment. The current study automates such judgments.Our novel wavelet-based algorithm automatically determines temporal extent and amplitude of the human soleus H-reflex and M-wave. In each of 20 participants, the algorithm was trained on data from a preliminary 3 or 4 min recruitment-curve measurement. Output was evaluated on parametric fits to subsequent sessions' recruitment curves (92 curves across all participants) and on the conditioning protocol's subsequent baseline trials (∼1200 per participant) performed near. Results were compared against the original temporal bounds estimated at the time, and against retrospective estimates made by an expert 6 years later.Automatic bounds agreed well with manual estimates: 95% lay within ±2.5 ms. The resulting H-reflex magnitude estimates showed excellent agreement (97.5% average across participants) between automatic and retrospective bounds regarding which trials would be considered successful for operant conditioning. Recruitment-curve parameters also agreed well between automatic and manual methods: 95% of the automatic estimates of the current required to elicitfell within±1.4%of the retrospective estimate; for the 'threshold' current that produced an M-wave 10% of maximum, this value was±3.5%.Such dependable automation of M-wave and H-reflex definition should make both established and emerging H-reflex protocols considerably less vulnerable to inter-personnel variability and human error, increasing translational potential.
Keywords: Electric Stimulation; Electromyography; H-Reflex; Humans; Muscle, Skeletal; Peripheral Nerves; Retrospective Studies

The Evoked Potential Operant Conditioning System (EPOCS): A Research Tool and an Emerging Therapy for Chronic Neuromuscular Disorders. - Hill, N Jeremy; Gupta, Disha; Eftekhar, Amir; Brangaccio, Jodi A; Norton, James J S; McLeod, Michelle; Fake, Tim; Wolpaw, Jonathan R; Thompson, Aiko K (J Vis Exp, 2022)
The Evoked Potential Operant Conditioning System (EPOCS) is a software tool that implements protocols for operantly conditioning stimulus-triggered muscle responses in people with neuromuscular disorders, which in turn can improve sensorimotor function when applied appropriately. EPOCS monitors the state of specific target muscles-e.g., from surface electromyography (EMG) while standing, or from gait cycle measurements while walking on a treadmill-and automatically triggers calibrated stimulation when pre-defined conditions are met. It provides two forms of feedback that enable a person to learn to modulate the targeted pathway's excitability. First, it continuously monitors ongoing EMG activity in the target muscle, guiding the person to produce a consistent level of activity suitable for conditioning. Second, it provides immediate feedback of the response size following each stimulation and indicates whether it has reached the target value. To illustrate its use, this article describes a protocol through which a person can learn to decrease the size of the Hoffmann reflex-the electrically-elicited analog of the spinal stretch reflex-in the soleus muscle. Down-conditioning this pathway's excitability can improve walking in people with spastic gait due to incomplete spinal cord injury. The article demonstrates how to set up the equipment; how to place stimulating and recording electrodes; and how to use the free software to optimize electrode placement, measure the recruitment curve of direct motor and reflex responses, measure the response without operant conditioning, condition the reflex, and analyze the resulting data. It illustrates how the reflex changes over multiple sessions and how walking improves. It also discusses how the system can be applied to other kinds of evoked responses and to other kinds of stimulation, e.g., motor evoked potentials to transcranial magnetic stimulation; how it can address various clinical problems; and how it can support research studies of sensorimotor function in health and disease.
Keywords: Chronic Disease; Conditioning, Operant; Electromyography; Evoked Potentials; H-Reflex; Humans; Neuromuscular Diseases; Spinal Cord Injuries

Soleus H-reflex modulation during a double-legged drop landing task. - Lyle, Mark A; McLeod, Michelle M; Pouliot, Bridgette A; Thompson, Aiko K (Exp Brain Res, 2022)
Muscle spindle afferent feedback is modulated during different phases of locomotor tasks in a way that facilitates task goals. However, only a few studies have studied H-reflex modulation during landing. This study aimed to characterize soleus (SOL) H-reflex modulation during the flight and early landing period of drop landings. Since landing presumably involves a massive increase in spindle afferent firing due to rapid SOL muscle stretching, we hypothesized H-reflex size would decrease near landing reflecting neural modulation to prevent excessive motoneuron excitation. The soleus H-reflex was recorded during drop landings from a 30 cm height in nine healthy adults. Electromyography (SOL, tibialis anterior (TA), medial gastrocnemius, and vastus lateralis), ankle and knee joint motion and ground reaction force were recorded during landings. Tibial nerve stimulation was timed to elicit H-reflexes during the flight and early ground contact period (five 30 ms Bins from 90 ms before to 60 ms after landing). The H-reflexes recorded after landing (0-30 and 30-60 ms) were significantly smaller (21-36% less) than that recorded during the flight periods (90-0 ms before ground contact; P ≤ 0.004). The decrease in H-reflex size not occurring until after ground contact indicates a time-critical modulation of reflex gain during the last 30 ms of flight (i.e., time of tibial nerve stimulation). H-reflex size reduction after ground contact supports a probable neural strategy to prevent excessive reflex-mediated muscle activation and thereby facilitates appropriate musculotendon and joint stiffness.
Keywords: Adult; Ankle Joint; Electromyography; H-Reflex; Humans; Muscle Spindles; Muscle, Skeletal

Targeted neuroplasticity for rehabilitation. - Thompson, Aiko K; Jonathan Wolpaw (Progress in Brain Research, 2015)
An operant-conditioning protocol that bases reward on the electromyographic response produced by a specific CNS pathway can change that pathway. For example, in both animals and people, an operant-conditioning protocol can increase or decrease the spinal stretch reflex or its electrical analog, the H-reflex. Reflex change is associated with plasticity in the pathway of the reflex as well as elsewhere in the spinal cord and brain. Because these pathways serve many different behaviors, the plasticity produced by this conditioning can change other behaviors. Thus, in animals or people with partial spinal cord injuries, appropriate reflex conditioning can improve locomotion. Furthermore, in people with spinal cord injuries, appropriate reflex conditioning can trigger widespread beneficial plasticity. This wider plasticity appears to reflect an iterative process through which the multiple behaviors in the individual's repertoire negotiate the properties of the spinal neurons and synapses that they all use. Operant-conditioning protocols are a promising new therapeutic method that could complement other rehabilitation methods and enhance functional recovery. Their successful use requires strict adherence to appropriately designed procedures, as well as close attention to accommodating and engaging the individual subject in the conditioning process.
Keywords: activity-dependent plasticity; H-Reflex; operant conditioning; Rehabilitation; spinal cord injury; spinal reflex

Operant conditioning of spinal reflexes: from basic science to clinical therapy. - Thompson, Aiko K; Jonathan Wolpaw (Front Integr Neurosci, 2014)
New appreciation of the adaptive capabilities of the nervous system, recent recognition that most spinal cord injuries are incomplete, and progress in enabling regeneration are generating growing interest in novel rehabilitation therapies. Here we review the 35-year evolution of one promising new approach, operant conditioning of spinal reflexes. This work began in the late 1970's as basic science; its purpose was to develop and exploit a uniquely accessible model for studying the acquisition and maintenance of a simple behavior in the mammalian central nervous system (CNS). The model was developed first in monkeys and then in rats, mice, and humans. Studies with it showed that the ostensibly simple behavior (i.e., a larger or smaller reflex) rests on a complex hierarchy of brain and spinal cord plasticity; and current investigations are delineating this plasticity and its interactions with the plasticity that supports other behaviors. In the last decade, the possible therapeutic uses of reflex conditioning have come under study, first in rats and then in humans. The initial results are very exciting, and they are spurring further studies. At the same time, the original basic science purpose and the new clinical purpose are enabling and illuminating each other in unexpected ways. The long course and current state of this work illustrate the practical importance of basic research and the valuable synergy that can develop between basic science questions and clinical needs.
Keywords: H-Reflex; learning and memory; Locomotion; spinal cord injury; spinal cord plasticity

The simplest motor skill: mechanisms and applications of reflex operant conditioning. - Thompson, Aiko K; Jonathan Wolpaw (Exerc Sport Sci Rev, 2014)
Operant conditioning protocols can change spinal reflexes gradually, which are the simplest behaviors. This article summarizes the evidence supporting two propositions: that these protocols provide excellent models for defining the substrates of learning and that they can induce and guide plasticity to help restore skills, such as locomotion, that have been impaired by spinal cord injury or other disorders.
Keywords: Animals; Conditioning, Operant; H-Reflex; Humans; Motor Skills; Muscle, Skeletal; Neuronal Plasticity; Reflex; Spinal Cord; Spinal Cord Injuries